Pengembangan Teknologi Probio_FM untuk Pengolahan Pupuk Organik pada Kelompok Peternak Sapi di Desa Lubuk Lingkuk, Kabupaten Bangka Tengah - Rufti Puji Astuti; Evahelda Evahelda; Nur Annis Hidayati (Institut Pertanian Bogor, 2020)
The integrated farming system between cattle and oil palm plantation provide both food source for cattle and fertilizer for the plant. This community partnership program aimed to give technical assistance to cattle farmers in producing organic fertilizer with probio_Fm technology. The activity was consisted of three steps, which were introduction, demonstration (laboratory and field demonstration), and control (monitoring and evaluation). The success of the program was qualitatively analysed. As a result, the Saling Gumilang cattle farmer group have been able to apply probio_Fm technology in cattle faeces composting. The farmers absorb 85% of the information given, which meant that the information was considered easy to be understood. As much as 50% of the farmers stated their preference in sustainable use of the probio_Fm technology. The farmers had shown their skills to produce organic fertilizer with probio_Fm technology without further asssitance. They produced one ton of organic fetilizer from cattle faeces with probio_Fm technology. The fertilizer had browny-blackish colour, weak undesirable odor, and loose texture. In the future, sustainable implementation of the probio_Fm technology is expected to optimize the cattle faeces composting in order to get a higher advantages of the integrated farming system between cattle and oil palm plantation.